GERAKAN SATU RUMAH SATU JUMANTIK (G1R1J) DALAM PERSPEKTIF IMPLEMENTASI KEBIJAKAN DI PUSKESMAS TALANG BAKUNG KOTA JAMBI - Indah Margarethy; Milana Salim (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2021)
G1R1J movement is an effort to prevent dengue hemorrhagic fever (DHF) which emphasizes community empowerment, especially the smallest unit in social life, namely the family. The purpose of this study is to describe how the implementation of G1R1J and its influencing factors in Jambi City. This research was a qualitative descriptive study where informants were determined by purposive sampling techniques and data collection is conducted with in-depth interviews. Test data validity using source triangulation technique methods and data analysis using content analysis. The results of this study indicate that one of the main factor that most influences the implementation of G1R1J in Jambi City has not run optimally is the absence of derivative regulations such as local government regulation where all items of G1R1J implementation can be described concretely in the regional regulation. This directly or indirectly has an impact on the aspects of communication, resources and organizational structure that have not run optimally to support the implementation of G1R1J in Jambi City. The positive disposition/response variable from policy makers and implementers in the field is a strength that the implementation of G1R1J will continue to run in the community of Jambi City.